(untitled) (Revista Sistemas de Producción Agroecológicos, 2019)
Agribusiness palm oil is the most promising country. Today for positioning a code in the seed market, it is important to have the data sheet for the product to market. The investigations conducted by Hacienda La Cabaña resulted in a new hybrid called Fortuna, which had higher fresh fruit yield and higher percentage of oil extraction. The aim of this study was to analyze physicochemically crude palm oil, interspecific hybrid Elaeis oleifera x Elaeis guineensis Coari La Mé, called Fortuna, to compare the results with theoretical values interspecific hybrid oil Classic and identify quality parameters of crude palm oil according to NTC 431. The results obtained with the traditional palm and the classic hybrid show that some fatty acid components retain their very similar relative values, however oil hybrid Fortuna code has more triglycerides containing oleic acid, and lower in palmitic acid.